The Influence of Regional Financial Accounting System Quality and Organizational Culture on Regional Government Performance in Rejang Lebong District - Yuni Maya Sari; Yuhanis Ladewi; Welly Welly; Rosalina Rosalina; Nunung Nurhayati (Kajian Akuntansi, 2023)
Abstract : This research was conducted to answer the problems that exist in the study of the quality of regional accounting systems and organizational culture on regional governments perrformance in Rejang Lebong Regency. The aim was to study the influence of the quality of regional financial accounting systems and organizational culture on regional governments perrformance in Rejang Lebong Regency. The type of this study was an associative and descriftive research. The research was conducted in the regional apparatus organization Rejang Lebong Regency. The variables used were the quality of regional financial accounting systems, organizational culture, and regional governments performance. The data used were primary data and secondary data. Data collection techniques used in this study were questionnaires and documentation. The data analysis methods used in this study were descriftive and inferensial statistic. Inferential statistical analysis consists of the classical assumption test, multiple regression tests, coefficient of determination, and the hypothesis test (t test) was computed by the Statistical Program for Special Science (SPSS). The results of the analysis showed there was a correlation between the quaulity of regional financial accounting systems and organizational culture on regional governments performance in Rejang Lebong Regency.